МОДЕЛЬ КООПЕРАТИВНОГО НАВЧАННЯ У ПРОЦЕСІ ВИВЧЕННЯ ІНОЗЕМНОЇ МОВИ (Modern Information Technologies and Innovation Methodologies of Education in Professional Training Methodology Theory Experience Problems, 2010)
The article deals with the problem of implementation of the cooperative learning model in the higher educational establishments as means of educational improvement. The author paid special attention to the concept of the cooperative learning model’s development, its separation from group learning model and to practical recommendations as to its usage in the process of learning the foreign language.